Octocoral Distribution Patterns at the Equatorial Front (Tropical Eastern Pacific): Muricea and Leptogorgia - Abad, Rubén (2022)
The Equatorial Front, in the southern part of the Tropical Eastern Pacific (TEP) region, has been characterized as a hotspot of functional biodiversity due to the mixing of warm and cold waters. Nevertheless, the biogeographic patterns for some organisms, such as octocorals, remain unknown in some coastal regions. Therefore, we aimed to assess the distribution of two common octocoral genera in this area, Muricea and Leptogorgia, including 14 species based on museum specimen records, along the mainland coast of Ecuador. Statistical analyses were performed on the environmental and geographical patterns (Sea Surface Temperature (SST), bathymetry, chlorophyll (CHL-a), and Photosynthetic Active Radiation (PAR)) that influence the Equatorial Front, which is subdivided into five biogeographic regions. Our results showed two hotspots of octocoral biodiversity. The SST was found to be the main environmental factor related to octocoral distribution along the Equatorial Front. Finally, the highest abundance of Muricea over Leptogorgia suggests the former species’ higher resilience to thermal fluctuations. We discuss the possible role of substrates at suitable depths, active photosynthetic radiation, and temperature in the occurrence of octocorals in the two hotspots.